Monitoring Polusi Udara Dan Kebakaran Berbasis Android - Fitri Nova; Andre Febrian Kasmar; Meri Azmi; Khaira Aprinaldo Putra (Elektron : Jurnal Ilmiah, 2021)
A fire in a building or office is one of the main cases that is currently being serious attention for businessmen and government agencies. Considering there are no activities in an office during nights and holidays, makes the business owners feel uncomfortable leaving the office. To overcome this problem, a sensor is to monitor a situation in the office whether there is a gas leak or a hotspot. It is hope that air pollution and fire monitoring tool can help to prevent fires. The way this tool works uses the Arduino Uno to retrieve data from the gas sensor and flame sensor. The data will be sent to the Ubidots server via NodeMCU ESP8266 as wifi or the internet. The monitoring display can be seen via Android and when there is an emergency, the ubidots server will immediately notify the room owner. The result shows that the effective distance of the sensor is around 10cm to 50 cm and the overall system runs well